The Molecules of Life: Physical and Chemical Principles - John Kuriyan, Boyana Konforti and David Wemmer (Garland Science, 2012)
This book helps with understanding of how life function by explaining the physical principles underpinning many complex biological phenomena, including how nerves transmit signals, the actions of chaperones in protein folding, and how polymerases and ribosomes achieve high fidelity. The central theme it that the ways in which proteins, DNA, and the RNA work together in a cell are connected intimately to the structures of these biological macromolecules. The structures, in turn, depend on interactions between the atoms in these molecules, and out he interplay between energy and entropy, which results in the remarkable ability of biological systems to self-assemble and control their own replication. By integrating fundamental concepts in thermodynamics at the level of molecular structure, this textbook provides a physical and biochemical foundation for undergraduate students majoring in biology or health sciences